2002
DOI: 10.1074/jbc.m202351200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of 17-β-Estradiol-induced Erk1/2 Activation in Breast Cancer Cells

Abstract: Activation of mitogen-activated protein kinase (Erk/ MAPK) is a critical signal transduction event for estrogen (E 2 )-mediated cell proliferation. Recent studies from our group and others have shown that persistent activation of Erk plays a major role in cell migration and tumor progression. The signaling mechanism(s) responsible for persistent Erk activation are not fully characterized, however. In this study, we have shown that E 2 induces a slow but persistent activation of Erk in MCF-7 breast carcinoma ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
137
4
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(146 citation statements)
references
References 63 publications
2
137
4
3
Order By: Relevance
“…One of the mechanisms by which cell lines develop resistance to antiestrogens is through the utilization of alternative signaling pathways that support cell growth in the presence of antiestrogens. Several different groups including our own have shown that PKC-d plays a major role in E2-mediated signaling (Shanmugam et al, 1999;Keshamouni et al, 2002). Based on the above data, we postulate that overexpression of PKC-d may be one of the adaptive mechanisms involved in Tam resistance in human breast tumor cells.…”
Section: Discussionmentioning
confidence: 86%
“…One of the mechanisms by which cell lines develop resistance to antiestrogens is through the utilization of alternative signaling pathways that support cell growth in the presence of antiestrogens. Several different groups including our own have shown that PKC-d plays a major role in E2-mediated signaling (Shanmugam et al, 1999;Keshamouni et al, 2002). Based on the above data, we postulate that overexpression of PKC-d may be one of the adaptive mechanisms involved in Tam resistance in human breast tumor cells.…”
Section: Discussionmentioning
confidence: 86%
“…The observation that Rottlerin alone or in combination with TPA led to a complete inhibition of growth also supports the conclusion that PKCd is a proproliferative or prosurvival factor in MELN cells. A role for active PKCd in promoting mammary tumour cell growth has been previously suggested by Keshamouni et al (2002), who described that cell growth induced by PKCd activation was inhibited by Rottlerin or a dominant-negative mutant of PKCd. In addition, the expression of the inhibitory PKCd regulatory domain inhibited growth in soft agar, cell motility and attachment in MTLn3 mammary tumour cells (Kiley et al, 1999b).…”
Section: Discussionmentioning
confidence: 99%
“…PKCd was upregulated by estradiol in corpus luteum (Maizels et al, 1996), while it was downregulated in MCF-7 cells in a time-and dose-dependent manner (Shanmugam et al, 1999). PKCd increased mammary tumour cell growth and metastasis by activation of the Ras/Erk1/2 pathway (Keshamouni et al, 2002). The activity of murine ERa was stimulated by PKCd and the effect required phosphorylation of serine 122 in the AF-1 region (Lahooti et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In addition to direct transcriptional effects, ERs localized to the plasma membrane can influence the activity of signalling pathways through coupling directly or indirectly to G-proteins by non-genomic mechanisms. 7 This leads to activation of downstream effectors such as protein kinase C-d, 9 mitogen activated protein kinase ERK (MAPK) 9,10,11 and phosphatidylinositol-3-OH kinase (PI3K). 12,13 Thus, ERa is a key player in E2-mediated proliferation, survival and differentiation through regulating the transcription of E2-target genes as well as through activation of signal transduction pathways.…”
Section: Introductionmentioning
confidence: 99%